Near-infrared Raman spectroscopy to detect anti-Toxoplasma gondii antibody in blood sera of domestic cats: quantitative analysis based on partial least-squares multivariate statistics - Duarte, Janaina; Pacheco, Marcos T. T.; Villaverde, Antonio Balbin; Machado, Rosangela Z. [UNESP]; Zangaro, Renato A.; Silveira, Landulfo (Spie-soc Photo-optical Instrumentation Engineers, 2010)
Toxoplasmosis is an important zoonosis in public health because domestic cats are the main agents responsible for the transmission of this disease in Brazil. We investigate a method for diagnosing toxoplasmosis based on Raman spectroscopy. Dispersive near-infrared Raman spectra are used to quantify anti-Toxoplasma gondii (IgG) antibodies in blood sera from domestic cats. An 830-nm laser is used for sample excitation, and a dispersive spectrometer is used to detect the Raman scattering. A serological test is performed in all serum samples by the enzyme-linked immunosorbent assay (ELISA) for validation. Raman spectra are taken from 59 blood serum samples and a quantification model is implemented based on partial least squares (PLS) to quantify the sample's serology by Raman spectra compared to the results provided by the ELISA test. Based on the serological values provided by the Raman/PLS model, diagnostic parameters such as sensitivity, specificity, accuracy, positive prediction values, and negative prediction values are calculated to discriminate negative from positive samples, obtaining 100, 80, 90, 83.3, and 100%, respectively. Raman spectroscopy, associated with the PLS, is promising as a serological assay for toxoplasmosis, enabling fast and sensitive diagnosis. (C) 2010 Society of Photo-Optical Instrumentation Engineers. [DOI: 10.1117/1.3463006]
Keywords: near-infrared Raman spectroscopy; multivariate statistical analysis; Partial Least Squares; Toxoplasmosis; Cat; Serology; indirect enzyme-linked immunosorbent assay